Pulsed Electromagnetic Fields Improve Tenogenic Commitment of Umbilical Cord-Derived Mesenchymal Stem Cells: A Potential Strategy for Tendon Repair-An In Vitro Study - Antonio Marmotti; Giuseppe Maria Peretti; Silvia Mattia; Laura Mangiavini; Laura de Girolamo; Marco Viganò; Stefania Setti; Davide Edoardo Bonasia; Davide Blonna; Enrico Bellato; Giovanni Ferrero; Filippo Castoldi (Hindawi Limited, 2018)
Tendon repair is a challenging procedure in orthopaedics. The use of mesenchymal stem cells (MSCs) and pulsed electromagnetic fields (PEMF) in tendon regeneration is still investigational. In this perspective, MSCs isolated from the human umbilical cord (UC) may represent a possible candidate for tendon tissue engineering. The aim of the study is to evaluate the effect of low-frequency PEMF on tenogenic differentiation of MSCs isolated from the human umbilical cord (UC-MSCs) in vitro. 15 fresh UC samples from women with healthy pregnancies were retrieved at the end of caesarean deliveries. UC samples were manually minced into small fragments (less than 4 mm length) and cultured in MSC expansion medium. Part of the UC-MSCs was subsequently cultured with PEMF and tenogenic growth factors. UC-MSCs were subjected to pulsed electromagnetic fields for 2 h/day, 4 h/day, or 8 h/day. UC-MSCs cultured with FGF-2 and stimulated with PEMF showed a greater production of collagen type I and scleraxis. The prolonged exposure to PEMF was also related to the greatest expression of tenogenic markers. Thus, the exposure to PEMF provides a positive preconditioning biophysical stimulus, which may enhance UC-MSC tenogenic potential.